Structural Perspective on Ancient Neuropeptide Y-like System reveals Hallmark Features for Peptide Recognition and Receptor Activation. Issue 13 (25th June 2021) - Gershkovich, Miron Mikhailowitsch; Groß, Victoria Elisabeth; Vu, Oanh; Schoeder, Clara Tabea; Meiler, Jens; Prömel, Simone; Kaiser, Anette
Graphical abstract: Highlights: Many peptide–GPCR signaling systems are evolutionary conserved down to basic animals. We illuminate binding of three distinct neuropeptide Y-like ligands in the FLP/NPR system of C. elegans. We identify E 5.23 (ECL2) and Q 3.32 of the receptors are family-conserved residues critical for affinity and efficacy. NanoBRET based ligand binding assays demonstrate flexibility of peptide ligands in the binding pocket. Comparing binding modes in evolutionary ancient homologs can identify key binding and activation mechanisms. Abstract: The neuropeptide Y (NPY) family is a peptide-activated G protein-coupled receptor system conserved across all bilaterians, and is involved in food intake, learning, and behavior. We hypothesized that comparing the NPY system in evolutionarily ancient organisms can reveal structural determinants of peptide recognition and receptor activation conserved in evolution. To test this hypothesis, we investigated the homologous FLP/NPR system of the protostome C. elegans . For three prototypic peptide–receptor complexes representing different ligand types, we integrate extensive functional data into structural models of the receptors. Common features include acidic patches in the extracellular loops (ECLs) of the receptors that cooperatively 'draw' the peptide into the binding pocket, which was functionally validated in vivo . A structurally conserved glutamate in the ECL2 anchors the peptides by a conserved salt bridge to the arginine of the RFamide motif. Beyond this conserved interaction, peptide binding show variability enabled by receptor-specific interactions. The family-conserved residue Q 3.32 is a key player for peptide binding and receptor activation. Altered interaction patterns at Q 3.32 may drastically increase the efficacy to activate the receptor.